WEB-BASED INFORMATION SYSTEM OF DATA COLLECTION AND DISTRIBUTION OF KEROSENE IN SANGIHE ISLANDS DISTRICT (CASE STUDY: AMT. UD GAMA) - Agimat, Thivania Philia; Langi, Yohanes Andreas Robert; Weku, Winsy Christo Deilan (Indonesian Journal of Intelligence Data Science, 2022)
Kerosene distribution, as one of the primary energy sources in island regions, often faces various challenges such as limited data, delayed delivery, and lack of transparency in recordkeeping. This study aims to develop a web-based information system for recording and managing kerosene distribution, implemented at the Kerosene Agent (AMT) UD GAMA in the Sangihe Islands Regency. The system is designed to assist in digitally recording stock data, distribution processes, and reporting, thereby minimizing errors and expediting decision-making. The system development method used is the waterfall model, consisting of requirement analysis, system design, implementation, testing, and evaluation stages. The results of system testing indicate that the application functions properly and meets user needs, both for the AMT and other related parties. The system is capable of recording distribution data in real-time, automatically generating distribution reports, and displaying stock information with high accuracy. Furthermore, users responded positively to its ease of access and simple user interface. Overall, the developed information system successfully improves operational efficiency, accountability, and transparency in kerosene distribution. Thus, the system can serve as a practical digital solution model for energy distribution management in island regions in a sustainable manner.